2023
DOI: 10.1186/s12905-023-02391-3
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of educational program based on health belief model on promotion of puberty health concepts among teen girls: a cross-sectional study in north of Iran

Sedighe Bab Eghbal,
Zahra Aghaei Kenari,
Asieh Ashouri
et al.

Abstract: Background Puberty is a sensitive critical stage of human life. As numerous healthy habits and behaviors are created during adolescence, correct health education during puberty is essential to maintain and improve an individual's physical, emotional, and mental health. The present study aimed to determine the impact of educational intervention based on the predictors of the Health Belief Model (HBM) on female nine-grade students’ health behaviors in Rasht, Iran. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Successful reproductive health education programs increase reproductive health knowledge and encourage positive behaviors (Eghbal et al, 2023;Pasay-an et al, 2020) Students with adequate knowledge of reproductive health require special attention as they near the conclusion of their social preparation for adulthood, according to a notable finding of this study. The increase in reproductive health knowledge is influenced not only by education but also by parental involvement in preparing children for maturity, according to previous research (Eghbal et al, 2023). Age is also regarded as a predictor of a person's level of maturity and comprehension of their sexual orientation.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Successful reproductive health education programs increase reproductive health knowledge and encourage positive behaviors (Eghbal et al, 2023;Pasay-an et al, 2020) Students with adequate knowledge of reproductive health require special attention as they near the conclusion of their social preparation for adulthood, according to a notable finding of this study. The increase in reproductive health knowledge is influenced not only by education but also by parental involvement in preparing children for maturity, according to previous research (Eghbal et al, 2023). Age is also regarded as a predictor of a person's level of maturity and comprehension of their sexual orientation.…”
Section: Resultsmentioning
confidence: 72%
“…Previous research has demonstrated that adolescents have a limited understanding of reproductive health, particularly with regard to menarche, menstruation, and menstrual hygiene (Eghbal et al, 2023). In the absence of accurate knowledge, negative attitudes and misconceptions about these topics can have negative effects on reproductive health.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown the limitations of adolescents in obtaining information about reproductive health knowledge, especially for menarche, menstruation, and personal hygiene [9]. Limited access to adequate information about reproductive knowledge often results in perceptions of negative attitudes and misunderstandings about menarche, menstruation, and menstruation-related hygiene, and this may have a negative impact on reproductive health.…”
Section: Fig 3 Community Service Team and The Target Communitymentioning
confidence: 99%
“…Adolescents' knowledge of healthy behavior can influence the way they behave and make decisions in their reproductive health life. Reproductive health education programs have been able to increase knowledge and behavior about reproductive health [9], [16].…”
Section: Fig 3 Community Service Team and The Target Communitymentioning
confidence: 99%
See 1 more Smart Citation